Progress and Development Prospect of Coalbed Methane (CBM) and Coal Rock Gas Exploration in China - Wang, Xiaolong; Liao, Siyi (Scientific Journal of Technology, 2025)
The backdrop of the accelerated advancement of the "dual carbon" goals and energy transition, coal rock gas, as a new type of unconventional natural gas resource, has emerged as a new highlight for increasing natural gas production and ensuring stable supply in China due to its enormous resource potential and unique development advantages. This paper systematically summarizes the major geological theoretical innovation achievements in China’s coal rock gas exploration field, outlines the resource potential and current status of exploration breakthroughs nationwide and in key basins, elaborates on the core progress of key technologies such as seismic exploration and drilling engineering, analyzes the main challenges facing current exploration and development, and finally looks forward to the future development direction. Research shows that China’s geological resources of coal rock gas exceed 50 trillion cubic meters, and an exploration trend of "multi-point breakthroughs and rapid growth" has been achieved. With the continuous upgrading of theories and technologies, it is expected to become an important strategic replacement resource for safeguarding national energy security.